G32(P) Ain't no party like a journal club party. (May 2019) - Wallace, S
Abstract : Aims: 100% of paediatric trainees must be able to critically appraise a study to complete paediatric training. We aimed for journal club to occur every 2 weeks within our general paediatric department; teaching trainees critical appraisal and improving evidence based medicine knowledge. Methods: We undertook a 24 week project using the model for improvement. Six plan-do-study-act (PDSA) cycles (table 1 ) were completed to introduce and sustain a journal club for paediatric trainees. Each intervention was evaluated based on the occurrence of a journal club session. An anonymous survey was sent to all trainees prior to starting the project to identify current journal club participation and areas for improvement (table 2 ). Results: Prior to starting the project a survey to paediatric trainees demonstrated that only 12% of trainees within our trust participated in a journal club; 34% were confident in critical appraisal. Assigning trainees to lead journal club without providing the necessary support e.g. critical appraisal teaching, signposting to appraisal tools or access to journals, resulted in no sessions occurring. The changes that lead to sustained occurrence were peer mentoring and support, and signposting to online tools. By week 24 a journal club session was occurring every 2 weeks, led by junior (ST1–3) and senior trainees (ST4–7). Conclusion: Providing paediatric trainees the opportunity to participate and lead journal club sessions is an essential part of training. Since 22nd July 2018 we have achieved 100% occurrence of journal club within our general paediatric department. Teaching, mentoring and entire team engagement ensured success.